Use of e-cigarettes and associated factors among adolescent smokers in Indonesia: Analysis of the Global Youth Tobacco Survey (GYTS) Indonesia 2019 - Marice, Marice; Kaseger, Henny; Hariyanti, Yunida; Hafid, Wahyuni; Purnamasari, Niluh Desy; Supetran, I Wayan; Akbar, Hairil; Maretalinia, Maretalinia (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Electronic cigarette (e-cigarette) is an alternative to reduce the harmfulness of conventional cigarettes. However, there are still pros and cons to using the e-cigarette, especially among adolescents. Instead of reducing the health problem, using e-cigarette even make the illness the same as conventional ones. Objective: This study aimed to examine the determinant of using e-cigarettes among adolescents and smokers of school age. Method: This study used the cross-sectional data from the Global Youth Tobacco Survey (GYTS) Indonesia 2019. The national school was selected by proportional random sampling. Around 832 adolescent smokers were eligible for this study. Results: Among 832 adolescent smokers in this study, about 49.64% of them ever used e-cigarettes. The factors significantly associated with the use of e-cigarettes were money pocket and the use of other forms of smoked tobacco. However, other independent variables, such as age, gender, teachers smoking during school hours, and parent smoking, were not significantly associated with using e-cigarettes. Conclusion: The factors associated with e-cigarette use were related to the students’ socioeconomic status. The roles of parents and teachers need to be addressed to reduce the harmfulness of using e-cigarettes.